Quality of life in patients with biliary tract diseases taking UDCAcontaining drug - A. M. Lukmanova; A. R. Isanbaeva; G. M. Sahautdinova (Лечащий Врач)
Background. When bile is oversaturated with cholesterol, the dynamic equilibrium between proand antinucleating factors is disturbed, which leads to precipitation of cholesterol crystals and their aggregation into microlites. Excess cholesterol is deposited in the gallbladder wall, where it strengthens the sarcolemmal membrane of smooth muscle cells and disrupts signal transmission. Slow emptying of gallbladder and bile stagnation occur, which increases its precipitation and formation of wall and then cavity biliary sludge. Bile acid preparations, in particular ursodeoxycholic acid, have litholytic action and are basic in treatment of biliary sludge.Objective. To evaluate and compare the quality of life of patients with biliary sludge taking drugs containing ursodeoxycholic acid. Materials and methods. The dynamics of clinical symptoms (biliary pain, dyspepsia, bitter taste in the mouth) and quality of life of 84 patients with biliary sludge receiving conservative therapy with various ursodeoxycholic acid preparations for three months were evaluated using the SF-36 Quality of Life questionnaire and the Biliary Symptom Severity Questionnaire.Results. After 3 months in patients with biliary sludge taking different ursodeoxycholic acid preparations, the indices of physical functioning, general condition, vital activity and mental health were studied, as well as the effectiveness of pain syndrome relief were compared by the indices of pain syndrome severity reduction and rapidity of pain relief when taking preparations containing ursodeoxycholic acid. Conclusion. Quality of life of patients with biliary sludge on the background of ursodeoxycholic acid preparations significantly improves. At the same time, relief of biliary symptoms leads to improvement of both physical and mental health indicators.